TAUP-2272-95


Distances on a one-dimensional lattice from noncommutative geometry

E. Atzmon
Raymond and Beverly Sackler Faculty of Exact Sciences,
School of Physics and Astronomy.
Tel - Aviv University
atzmon@ccsg.tau.ac.il
(July 2, 1995)
Abstract

In the following paper we continue the work of Bimonte-Lizzi-Sparano[1] on distances on a one dimensional lattice. We succeed in proving analytically the exact formulae for such distances. We find that the distance to an even point on the lattice is the geometrical average of the “predecessor” and “successor” distances to the neighbouring odd points.

1 Distances on a one dimensional lattice from noncommutative geometry

The distance between two points a and b on a given space, is defined, from the geometrical point of view as the infimum of all lengths of paths connecting the two points on that space.

d(a,b)=inflα(a,b)𝑑𝑎𝑏infimumsubscript𝑙𝛼𝑎𝑏d(a,b)=\;\inf\;l_{\alpha}\left(a,b\right) (1)

where lαsubscript𝑙𝛼l_{\alpha}\;is the length of the path α𝛼\alpha\;which connects the points a𝑎a and b𝑏b. This definition is simple and well understood, when dealing with smooth metric manifolds. However the above definition is not applicable to discrete spaces in which the term “path” is not well defined. In order to be able to define a distance on such spaces too, one has to use tools other than the usual geometrical ones. Those tools are found in noncommutative geometry (n.c.g). The n.c.g definition for distance is:[2]

d(a,b)=supf{|f(a)f(b)|:fA,[D,f]1}d(a,b)=\sup_{f}\left\{\left|f(a)-f(b)\right|\;:\;f\in A,\;\left\|\;\left[\;D,f\;\right]\;\right\|\leq 1\right\} (2)

where a,bX,fA,formulae-sequence𝑎𝑏𝑋𝑓𝐴a,b\in X,\;f\in A, A𝐴A is the algebra of functions on X,𝑋X, D𝐷D is a Dirac operator (which is a self adjoint operator with compact resolvent) acting in the Hilbert space H,𝐻H, and the norm on the r.h.s is the norm of operators in H𝐻H. Both definitions give the same result when the base space is a Riemannian manifold. However the n.c.g definition has the advantage of being applicable to discrete spaces too.

In the following we continue the work of Ref[1] (which we denote “BLS”) by finding and proving the exact formula for distances on a one dimensional lattice. We use the BLS notation. As a first step we summarize briefly the BLS work relevant to a one dimensional lattice.

A one dimensional lattice is defined as:

xk=ak,kZformulae-sequencesubscript𝑥𝑘𝑎𝑘𝑘𝑍x_{k}=ak,\quad k\in Z (3)

In order to compute the distance between two point x0subscript𝑥0x_{0} and xksubscript𝑥𝑘x_{k} one has first to define the Dirac operator. BLS used the Wilson definition for a Dirac operator:

(DΨ)x=12ia(Ψx+1Ψx1)subscript𝐷Ψ𝑥12𝑖𝑎subscriptΨ𝑥1subscriptΨ𝑥1\left(D\Psi\right)_{x}=\frac{1}{2ia}\left(\Psi_{x+1}-\Psi_{x-1}\right) (4)

where D𝐷D acts on the Hilbert space of square integrable spinors ΨΨ\Psi (ΨL2)Ψsubscript𝐿2\;\left(\Psi\in L_{2}\right), and x𝑥x is a site on the one dimensional lattice. Let f𝑓f act on the Hilbert space as a linear operator. It is shown that in order to get the supremum it is enough to take the supremum over the set of real functions:

f(k){fi(k);iZ}f^{\left(k\right)}\equiv\left\{f_{i}^{\left(k\right)}\quad;\quad i\in Z\right\} (5)

such that:

a) fi(k)=f0(k)i<0b) fi(k)=fk(k)i>kc) fi(k)fj(k)i<jd) [D,f(k)]1formulae-sequencea) superscriptsubscript𝑓𝑖𝑘superscriptsubscript𝑓0𝑘for-all𝑖0formulae-sequenceb) superscriptsubscript𝑓𝑖𝑘superscriptsubscript𝑓𝑘𝑘for-all𝑖𝑘formulae-sequencec) superscriptsubscript𝑓𝑖𝑘superscriptsubscript𝑓𝑗𝑘for-all𝑖𝑗d) norm𝐷superscript𝑓𝑘1\begin{array}[]{l}\mbox{a)\qquad}f_{i}^{\left(k\right)}=f_{0}^{\left(k\right)}\quad\forall\;i<0\\ \mbox{b)\qquad}f_{i}^{\left(k\right)}=f_{k}^{\left(k\right)}\quad\forall\;i>k\\ \mbox{c)\qquad\ }f_{i}^{\left(k\right)}\leq f_{j}^{\left(k\right)}\quad\forall\;i<j\\ \mbox{d)\qquad}\left\|\left[D\;,\;f^{\left(k\right)}\right]\right\|\leq 1\end{array} (6)

BLS then show that, following Eq.(2),(6) the distance becomes :

dk=sup{fk(k)f0(k):[D,f(k)]1}subscript𝑑𝑘supremumconditional-setsuperscriptsubscript𝑓𝑘𝑘superscriptsubscript𝑓0𝑘norm𝐷superscript𝑓𝑘1d_{k}=\sup\left\{f_{k}^{\left(k\right)}-f_{0}^{\left(k\right)}\;\;:\;\left\|\left[D\;,\;f^{\left(k\right)}\right]\right\|\leq 1\right\} (7)

where the norm on the r.h.s is equal to the maximum eigenvalue r𝑟r of a square, symmetric and real “three-diagonal” matrix  H(k) :

(0Δ1000Δ10Δ2000Δ20000Δk000Δk0)0subscriptΔ1000subscriptΔ10subscriptΔ2000subscriptΔ20000subscriptΔ𝑘000subscriptΔ𝑘0\left(\begin{array}[]{ccccc}0&\Delta_{1}&0&0&0\\ \Delta_{1}&0&\Delta_{2}&0&0\\ 0&\Delta_{2}&0&\ddots&0\\ 0&0&\ddots&\ddots&\Delta_{k}\\ 0&0&0&\Delta_{k}&0\end{array}\right) (8)

where Δi=fi(k)fi1(k)subscriptΔ𝑖superscriptsubscript𝑓𝑖𝑘superscriptsubscript𝑓𝑖1𝑘\Delta_{i}=f_{i}^{\left(k\right)}-f_{i-1}^{\left(k\right)} .

Since all the elements of H(k) are not negative, one can use a theorem[3] according to which, in such case the maximum eigenvalue of H(k) is less than 1, if and only if, all the leading principal minors H(Δ1,,Δn1)n{}_{n}\left(\Delta_{1},\ldots,\Delta_{n-1}\right) where n=1,,k+1𝑛1𝑘1n=1,\ldots,k+1 of the matrix  I\;-\;H are positive :

H1(k)=1>0,,Hi(k)>0,,Hk(k)>0,Hk+1(k)=det(I(k)H(k))=0formulae-sequencesuperscriptsubscriptH1𝑘10superscriptsubscriptH𝑖𝑘0superscriptsubscriptH𝑘𝑘0superscriptsubscriptH𝑘1𝑘superscriptI𝑘superscriptH𝑘0\mbox{H}_{1}^{\left(k\right)}=1>0,\ldots,\mbox{H}_{i}^{\left(k\right)}>0,\ldots,\mbox{H}_{k}^{\left(k\right)}>0,\;\mbox{H}_{k+1}^{\left(k\right)}=\det\left(\mbox{I}^{\left(k\right)}\;-\;\mbox{H}^{\left(k\right)}\right)=0 (9)

It is then shown that in order to find the distance, i.e. the supremum of iisubscript𝑖subscript𝑖\sum_{i}\triangle_{i} satisfying all conditions set by (9), one can use the method of Lagrange multipliers, and solve the following set of equations in the unknowns (1(k+1)k(k+1))superscriptsubscript1𝑘1superscriptsubscript𝑘𝑘1\left(\triangle_{1}^{\left(k+1\right)}\ldots\triangle_{k}^{\left(k+1\right)}\right)\;and α𝛼\alpha\;(the Lagrange multiplier) :

{j[i=1ki+αHk+1(k)]j=j(k+1)=0,jkHk+1(k)=0}formulae-sequencesubscript𝑗subscriptdelimited-[]superscriptsubscript𝑖1𝑘subscript𝑖𝛼superscriptsubscriptH𝑘1𝑘subscript𝑗superscriptsubscript𝑗𝑘10for-all𝑗𝑘superscriptsubscriptH𝑘1𝑘0\left\{\begin{array}[]{l}\frac{\partial}{\partial\triangle_{j}}\left[\sum_{i=1}^{k}\triangle_{i}+\alpha\mbox{H}_{k+1}^{\left(k\right)}\right]_{\triangle_{j}=\triangle_{j}^{\left(k+1\right)}}=0,\qquad\forall\;\;j\leq k\\ \mbox{H}_{k+1}^{\left(k\right)}=0\end{array}\right\} (10)

to find what the distance is.

In the following we solve exactly the above equations.

2 Exact solution

As the first step in solving the above equations we have to use some of the properties of real, symmetric, three-diagonal matrices:

The first property is :

Hk+1=Hkk2Hk1subscriptH𝑘1subscriptH𝑘superscriptsubscript𝑘2subscriptH𝑘1\mbox{H}_{k+1}=\mbox{H}_{k}-\triangle_{k}^{2}\mbox{H}_{k-1} (11)

from which it follows that:

a) k=(HkHk+1Hk1)12 if  Hk10b) kHk+1=2kHk1k(because there is no k in  Hk)c) k1Hk+1=k1Hkk(because there is no k1 in  Hk1)a) subscript𝑘superscriptsubscriptH𝑘subscriptH𝑘1subscriptH𝑘112subscript if  H𝑘10missing-subexpressionb) subscript𝑘subscriptH𝑘12subscript𝑘subscriptH𝑘1for-all𝑘(because there is no subscript𝑘subscript in  H𝑘)missing-subexpressionc) subscript𝑘1subscriptH𝑘1subscript𝑘1subscriptH𝑘for-all𝑘(because there is no subscript𝑘1subscript in  H𝑘1)\begin{array}[]{l}\mbox{a)\ \ \ }\triangle_{k}=\left(\frac{\mbox{H}_{k}-\mbox{H}_{k+1}}{\mbox{H}_{k-1}}\right)^{\frac{1}{2}}\mbox{\qquad if \ H}_{k-1}\neq 0\\ \\ \mbox{b)\ \ \ \ }\frac{\partial}{\partial\triangle_{k}}\mbox{H}_{k+1}=-2\triangle_{k}\mbox{H}_{k-1}\qquad\forall\;k\\ \mbox{(because there is no\ }\triangle_{k}\mbox{ \ in \ H}_{k}\mbox{)}\\ \\ \mbox{c)\ \ \ \ }\frac{\partial}{\partial\triangle_{k-1}}\mbox{H}_{k+1}=\frac{\partial}{\partial\triangle_{k-1}}\mbox{H}_{k}\qquad\forall\;k\\ \mbox{(because there is no\ }\triangle_{k-1}\mbox{\ \ in \ H}_{k-1}\mbox{)}\end{array} (12)

We now make use of the fact that :

xdetAk+1=i=1k+1Ai,k+1(x)𝑥subscript𝐴𝑘1superscriptsubscript𝑖1𝑘1superscriptsubscript𝐴𝑖𝑘1𝑥\frac{\partial}{\partial x}\det A_{k+1}=\sum_{i=1}^{k+1}A_{i,k+1}^{\left(x\right)} (13)

where Ak+1subscript𝐴𝑘1A_{k+1} is a (k+1)×(k+1)𝑘1𝑘1\left(k+1\right)\times\left(k+1\right) matrix and :

Ai,k+1(x)det(()1ji1(x,,x)j=i()k+1ji+1)A_{i,k+1}^{\left(x\right)}\equiv\det\left(\begin{array}[]{l}\left(\;\;\;\;\;\;\;\vdots\;\;\;\;\;\;\right)_{1\leq j\leq i-1}\\ \left(\frac{\partial}{\partial x},\ldots,\frac{\partial}{\partial x}\right)_{j=i}\\ \left(\;\;\;\;\;\;\;\vdots\;\;\;\;\;\;\right)_{k+1\geq j\geq i+1}\end{array}\right) (14)

i.e. a determinant of the matrix where the derivation is imposed on the i𝑖\;i th𝑡-th  row.

However since  I - H  is also a three-diagonal matrix, jsubscript𝑗\;\triangle_{j}  is found only in the jth𝑗𝑡\;j-th  and (j+1)th𝑗1𝑡\;(j+1)-th  rows. One thus gets :

jHk+1=Hj,k+1(j)+Hj+1,k+1(j)subscript𝑗subscriptH𝑘1superscriptsubscriptH𝑗𝑘1subscript𝑗superscriptsubscriptH𝑗1𝑘1subscript𝑗\frac{\partial}{\partial\triangle_{j}}\mbox{H}_{k+1}=\mbox{H}_{j,k+1}^{\left(\triangle_{j}\right)}+\mbox{H}_{j+1,k+1}^{\left(\triangle_{j}\right)} (15)

One can show (using an even number of inter-changes between rows and columns) that: H=j,k+1(j){}_{j,k+1}^{\left(\triangle_{j}\right)}=  H(j)j+1,k+1superscriptsubscriptabsent𝑗1𝑘1subscript𝑗{}_{j+1,k+1}^{\left(\triangle_{j}\right)}, yielding,

jHk+1=2jHj,k+1(j)=2jHj+1,k+1(j)subscript𝑗subscriptH𝑘12subscript𝑗superscriptsubscriptH𝑗𝑘1subscript𝑗2subscript𝑗superscriptsubscriptH𝑗1𝑘1subscript𝑗\frac{\partial}{\partial\triangle_{j}}\mbox{H}_{k+1}=-2\triangle_{j}\mbox{H}_{j,k+1}^{\left(\triangle_{j}\right)}=-2\triangle_{j}\mbox{H}_{j+1,k+1}^{\left(\triangle_{j}\right)} (16)

And by using the block structure of  H(j)j,k+1superscriptsubscriptabsent𝑗𝑘1subscript𝑗{}_{j,k+1}^{\left(\triangle_{j}\right)}  one gets that :

jHk+1=2jHj1(1,,j2)Hkj(iki+1:ikj1)\frac{\partial}{\partial\triangle_{j}}\mbox{H}_{k+1}=-2\triangle_{j}\mbox{H}_{j-1}\left(\triangle_{1,}\ldots,\triangle_{j-2}\right)\cdot\mbox{H}_{k-j}\left(\triangle_{i}\rightarrow\triangle_{k-i+1}\;:\;\forall\;i\leq k-j-1\right) (17)

but since it was shown[1] that the maximum is unique, and since the equations (10) have a symmetry under  iki+1subscript𝑖subscript𝑘𝑖1\triangle_{i}\longleftrightarrow\triangle_{k-i+1}   the solution must fix i=ki+1subscript𝑖subscript𝑘𝑖1\;\triangle_{i}=\triangle_{k-i+1}. Thus what one essentially gets is simply that:

jHk+1=2jHj1Hkjsubscript𝑗subscriptH𝑘12subscript𝑗subscriptH𝑗1subscriptH𝑘𝑗\frac{\partial}{\partial\triangle_{j}}\mbox{H}_{k+1}=-2\triangle_{j}\mbox{H}_{j-1}\mbox{H}_{k-j} (18)

Equations (10) take the following form:

{12αjHj1Hkj=0}1jkHk+1=0subscript12𝛼subscript𝑗subscriptH𝑗1subscriptH𝑘𝑗01𝑗𝑘subscriptH𝑘10\begin{array}[]{c}\left\{\begin{array}[]{c}1-2\alpha\triangle_{j}\mbox{H}_{j-1}\mbox{H}_{k-j}=0\\ \vdots\end{array}\right\}_{1\leq j\leq k}\\ \mbox{H}_{k+1}=0\end{array} (19)

It can be verified, that if  Hk-1  and  Hk  are both 0absent0\;\neq 0, it follows from the last equation that  k=(HkHk1)12subscript𝑘superscriptsubscriptH𝑘subscriptH𝑘112\triangle_{k}=\left(\frac{\mbox{H}_{k}}{\mbox{H}_{k-1}}\right)^{\frac{1}{2}};  while from the  j=k𝑗𝑘j=k\;\;equation one gets, α=12HkHk1𝛼12subscriptH𝑘subscriptH𝑘1\;\alpha=\frac{1}{2\sqrt{\mbox{H}_{k}\mbox{H}_{k-1}}}  .

Until now what we have done is just to simplify the equations that we have to solve. From now on we assume what the solutions for the unknowns should be. Since the solution is unique, then by setting the assumed solutions (i.e. the  isubscript𝑖\triangle_{i}\;\;’s) into the set of equations (19) and showing that they really solve the equations, we are essentially proving that the assumed solutions are correct. Knowing the solutions for the  isubscript𝑖\triangle_{i} ’s one can then find what the distance is. As the first case we will solve for k=𝑘absentk= even.

2.1 The k=even𝑘𝑒𝑣𝑒𝑛\;k=even  case

Let us assume that the solution for the isubscript𝑖\;\triangle_{i}\;’s is:

i(k)=12(1(1)i)(k2+1)+(1)i[i+12]k2(k2+1)ikformulae-sequencesuperscriptsubscript𝑖𝑘121superscript1𝑖𝑘21superscript1𝑖delimited-[]𝑖12𝑘2𝑘21for-all𝑖𝑘\triangle_{i}^{\left(k\right)}=\frac{\frac{1}{2}\left(1-\left(-1\right)^{i}\right)\left(\frac{k}{2}+1\right)+\left(-1\right)^{i}\left[\frac{i+1}{2}\right]}{\sqrt{\frac{k}{2}\left(\frac{k}{2}+1\right)}}\;\;\;\;\forall\;i\leq k (20)

where the []\left[\;\right]\;\;bracket stand for the integral value of the term within; and the Lagrange multiplier is :

α(k)=[k(k+2)]k122k1k[(k21)!]2superscript𝛼𝑘superscriptdelimited-[]𝑘𝑘2𝑘12superscript2𝑘1𝑘superscriptdelimited-[]𝑘212\alpha^{\left(k\right)}=\frac{\left[k\left(k+2\right)\right]^{\frac{k-1}{2}}}{2^{k-1}k\left[\left(\frac{k}{2}-1\right)!\right]^{2}} (21)

By using the recursion relation (11), and from the fact that  H=0{}_{0}=H=11{}_{1}=1\;\;, one can prove by induction that:

H2l+1(k)=22ll!(k21)![k(k+2)]l(k2l1)!: 1lk2(Hk+1=0)\mbox{H}_{2l+1}^{(k)}=\frac{2^{2l}l!\left(\frac{k}{2}-1\right)!}{\left[k\left(k+2\right)\right]^{l}\left(\frac{k}{2}-l-1\right)!}\;\;\;\;\;:\;1\leq l\leq\frac{k}{2}\;\;\;\;\;\;\left(\Rightarrow\;\mbox{H}_{k+1}=0\right) (22)

and

H2l(k)=22ll!(k2)![k(k+2)]l(k2l)!: 1lk2\mbox{H}_{2l}^{\left(k\right)}=\frac{2^{2l}l!\left(\frac{k}{2}\right)!}{\left[k\left(k+2\right)\right]^{l}\left(\frac{k}{2}-l\right)!}\;\;\;\;\;\;\;:\;1\leq l\leq\frac{k}{2} (23)

We now have all the ingredients we need for the equations. All we have to do is to check that essentially all the equations are fulfilled; and indeed they are, as can be verified by a few arithmetical steps.

After proving that the isubscript𝑖\triangle_{i}\;’s  are the solution for the set of equations (19) we can now find exactly, that the distance in the k=even𝑘𝑒𝑣𝑒𝑛k=even\;\;case is :

dk=2ai=1ki(k)=2ak2(k2+1)=ak(k+2)subscript𝑑𝑘2𝑎superscriptsubscript𝑖1𝑘superscriptsubscript𝑖𝑘2𝑎𝑘2𝑘21𝑎𝑘𝑘2d_{k}=2a\cdot\sum_{i=1}^{k}\triangle_{i}^{\left(k\right)}=2a\cdot\sqrt{\frac{k}{2}\left(\frac{k}{2}+1\right)}=a\sqrt{k\left(k+2\right)} (24)

Q.E.D. for the k=even𝑘𝑒𝑣𝑒𝑛k=even case.

2.2 The k=odd𝑘𝑜𝑑𝑑k=odd  case :

Let us assume that the solution in this case has the following structure:

2i+1(k)=(1ε)2i(k)=εα(k)=12εk12(1ε)k+12superscriptsubscript2𝑖1𝑘1𝜀missing-subexpressionsuperscriptsubscript2𝑖𝑘𝜀missing-subexpressionsuperscript𝛼𝑘12superscript𝜀𝑘12superscript1𝜀𝑘12\begin{array}[]{l}\triangle_{2i+1}^{\left(k\right)}=\left(1-\varepsilon\right)\\ \\ \triangle_{2i}^{\left(k\right)}=\varepsilon\\ \\ \alpha^{\left(k\right)}=\frac{1}{2\varepsilon^{\frac{k-1}{2}}\left(1-\varepsilon\right)^{\frac{k+1}{2}}}\end{array} (25)

and let us also assume temporarily that  H=1(k)1ε{}_{1}^{\left(k\right)}=1-\varepsilon. It is easy to show by the recursion relation (11) that:

H2j(k)=εj(1ε)jH2j+1(k)=εj(1ε)j+1 0jk12superscriptsubscriptH2𝑗𝑘superscript𝜀𝑗superscript1𝜀𝑗missing-subexpressionsuperscriptsubscriptH2𝑗1𝑘superscript𝜀𝑗superscript1𝜀𝑗1for-all 0𝑗𝑘12\begin{array}[]{l}\mbox{H}_{2j}^{\left(k\right)}=\varepsilon^{j}\left(1-\varepsilon\right)^{j}\\ \\ \mbox{H}_{2j+1}^{\left(k\right)}=\varepsilon^{j}\left(1-\varepsilon\right)^{j+1}\end{array}\;\forall\;0\leq j\leq\frac{k-1}{2} (26)

The solutions can now be set into the equations (19). It is easy to verify that those solutions obey the set of equations. However since we know that  H=1(k)1{}_{1}^{\left(k\right)}=1  (rather then 1ε1𝜀1-\varepsilon)  one has to take the limit where ε0+𝜀superscript0\varepsilon\rightarrow 0^{+}.  Thus, when the limit ε0+𝜀superscript0\;\varepsilon\rightarrow 0^{+}  is applied, it follows that:

H0(k)=H1(k)=1,Hj(k)=0j2formulae-sequencesuperscriptsubscriptH0𝑘superscriptsubscriptH1𝑘1superscriptsubscriptH𝑗𝑘0for-all𝑗2\mbox{H}_{0}^{\left(k\right)}=\mbox{H}_{1}^{\left(k\right)}=1,\;\;\;\mbox{H}_{j}^{\left(k\right)}=0\;\;\forall\;j\geq 2 (27)

which means that all the conditions in Eq.(9) are fulfilled. Taking the limit ε0+𝜀superscript0\varepsilon\rightarrow 0^{+}  it follows that:

2j+1=12j=0α 0jk12subscript2𝑗11missing-subexpressionsubscript2𝑗0missing-subexpression𝛼for-all 0𝑗𝑘12\begin{array}[]{c}\triangle_{2j+1}=1\\ \\ \triangle_{2j}=0\\ \\ \alpha\rightarrow\infty\end{array}\;\forall\;0\leq j\leq\frac{k-1}{2} (28)

We were able to use the limiting procedure, through the fact that this is a supremum problem - so we just had to prove that the limit exists. By that we have essentially proven that the solutions are as listed in Eq.(28).

Having all the i(k)superscriptsubscript𝑖𝑘\triangle_{i}^{\left(k\right)}\;’s we can find that the distance in the k=odd𝑘𝑜𝑑𝑑k=odd case is:

dk=2ai=1ki(k)=a(k+1)subscript𝑑𝑘2𝑎superscriptsubscript𝑖1𝑘superscriptsubscript𝑖𝑘𝑎𝑘1d_{k}=2a\sum_{i=1}^{k}\triangle_{i}^{\left(k\right)}=a\left(k+1\right) (29)

Q.E.D. for the k=odd𝑘𝑜𝑑𝑑k=odd case.

We can summarize that the distances in the lattice are:

{d2j1=2ajd2j=2aj(j+1)}subscript𝑑2𝑗12𝑎𝑗missing-subexpressionsubscript𝑑2𝑗2𝑎𝑗𝑗1\left\{\begin{array}[]{l}d_{2j-1}=2aj\\ \\ d_{2j}=2a\sqrt{j\left(j+1\right)}\end{array}\right\} (30)

3 Discussion

3.1 Mathematical aspects

All distances have anomalous behavior, as compared to what one expects classically. The anomaly in the odd point distances is exactly equal to one. The anomaly in the even point distances depends on the points. These are non-constant, irrational numbers, smaller than one, which asymptotically tend to 1.

The second outcome from (30) is that the distance to an even point is the geometrical average of the distances to the nearby predecessor and successor odd points (rather than an arithmetical average which one would have expected classically).

Concerning the large k𝑘k  limit, it follows where k=2j𝑘2𝑗k=2j\rightarrow\infty  the distance to an even point k=2j𝑘2𝑗k=2j  has the following behavior:

2aj(j+1)  2aj(1+12j)2𝑎𝑗𝑗12𝑎𝑗112𝑗2a\sqrt{j\left(j+1\right)}\longrightarrow\;\;2aj\left(1+\frac{1}{2j}\right) (31)

One can thus see that the asymptotic behavior of the even point distances becomes the same as for the odd point distances (in other words the geometrical average asymptotically tends to the arithmetical average).

3.2 Physical aspects

One can say that the cause for the results we got to be different from what one might expect, is an outcome of using the local discrete Wilson - Dirac operator. One should perhaps try non-local Dirac operator in order to get the classical behavior that we expect.

However as far as the physical world is concerned, we have shown that asymptotically, in the large k𝑘k limit, the differnce in behavior of the odd point distances and the even point distances on the lattice vanishes. Usually in nature one deals with lattices with very large k𝑘k. Thus all these effects are not seen. One could treat the lattice as a ”quantum” system, in which the quantum behavior of nature is revealed for small k𝑘k, and for large k𝑘k the classical behavior is reached asymptotically (We remind the reader that the n.c.g definition for distance considers not only the base space, but also the Hilbert space). Thus, following this point of view, one can continue working with the local Wilson - Dirac operator, though revealing non-classical behavior of the lattice.

Acknowledgments

I would like to thank Prof. Y. Ne’eman, Prof. F. Lizzi and Mr. O. Kennet for useful discussions.

References

  • [1] G. Bimonte, F. Lizzi, G. Sparano, Distances on a lattice from noncommutative geometry. Phys. Lett. B 341 (1994) 139-146
  • [2] A. Connes, Noncommutative Geometry, Academic Press, Inc. 1994
  • [3] F.R. Gantmacher, Applications of the Theory of Matrices, Interscience, New York, 1959.